2011
DOI: 10.1161/hypertensionaha.110.166827
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Pressure-Natriuresis and Renal Autoregulation

Abstract: Abstract-Sexual dimorphism in arterial pressure regulation has been observed in humans and animal models. The mechanisms underlying this gender difference are not fully known. Previous studies in rats have shown that females excrete more salt than males at a similar arterial pressure. The renin-angiotensin system is a powerful regulator of arterial pressure and body fluid volume. This study examined the role of the angiotensin type 2 receptor (AT 2 R) in pressure-natriuresis in male and female rats because AT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
112
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 40 publications
10
112
3
Order By: Relevance
“…7 This observation of a sex-specific renal vascular response to C21 in the present study is consistent with our previous observations in rodents that AT 2 R plays a greater functional role in female than in male renal vasculature, providing protection against the vasoconstrictor effects of AngII. 5,6,8 Furthermore, our data support the notion that differences in the renal response to C21 between male and female SHRs is attributable to sex differences in renal AT 2 R expression. We observed significantly greater basal AT 2 R mRNA expression in the kidneys of female SHRs as compared with male SHRs, in agreement with the previous findings of Silva-Antonialli et al 2 In addition, although we observed significantly greater renal angiotensin type 1a receptor expression in female SHRs as compared with their male counterparts, the relative AT 2 R-to-AT 1 R ratio was much greater in female than in male SHRs, although such sex differences in basal renal AT 1 R or AT 2 R mRNA expression are not always reported.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…7 This observation of a sex-specific renal vascular response to C21 in the present study is consistent with our previous observations in rodents that AT 2 R plays a greater functional role in female than in male renal vasculature, providing protection against the vasoconstrictor effects of AngII. 5,6,8 Furthermore, our data support the notion that differences in the renal response to C21 between male and female SHRs is attributable to sex differences in renal AT 2 R expression. We observed significantly greater basal AT 2 R mRNA expression in the kidneys of female SHRs as compared with male SHRs, in agreement with the previous findings of Silva-Antonialli et al 2 In addition, although we observed significantly greater renal angiotensin type 1a receptor expression in female SHRs as compared with their male counterparts, the relative AT 2 R-to-AT 1 R ratio was much greater in female than in male SHRs, although such sex differences in basal renal AT 1 R or AT 2 R mRNA expression are not always reported.…”
Section: Discussionsupporting
confidence: 84%
“…Acute systemic blockade of AT 2 R shifted the pressure-natriuresis relationship rightwards in both female and male rats. 5 Moreover, AT 2 R blockade blunted the autoregulation of renal blood flow (RBF) and glomerular filtration rate (GFR) at low renal perfusion pressures and enhanced the renal vasoconstrictor response to AngII in female rats only. 5 This led to our conclusion that AT 2 R modulates sodium excretion in both sexes and may contribute to the mechanisms by which female sex is protected against AngII-induced vascular alterations and hypertension.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have also recently reported that the AT 2 R has a significant role in the control of renal function. 7,8 We showed that direct AT 2 R stimulation using C21 has a pronounced influence on renal excretory and hemodynamic function, albeit in normotensive rats using a substantially lower dose (0.028 mg kg À1 per minute). 8 Remarkably, in both studies, the renal response to C21 was observed without any inhibition of AT 1 R function, demonstrating the ability of AT 2 R agonism to directly modulate renal function.…”
mentioning
confidence: 92%
“…We have also recently reported that the AT 2 R has a significant role in the control of renal function. 7,8 …”
mentioning
confidence: 99%